Hubungan Indeks Massa Tubuh dan Jenis Kelamin Terhadap Body Image Dissatisfaction (Ketidakpuasan Gambaran Tubuh) pada Siswa/Siswi SMA Methodist 1 Medan - Panjaitan, Bintang Andika; Tarigan, Mawar Gloria; Pakpahan, Edwin Anto; Situmorang, Nasib Mangoloi; Siagian, Laura Octavina (Majalah Ilmiah METHODA, 2024)
Body dissatisfaction is defined as an individual's dissatisfaction with their body shape, which often leads to low self-confidence, feelings of shame, and social withdrawal. Students who experience body dissatisfaction tend to engage in excessive dieting and extreme exercise in response to this dissatisfaction. Factors that contribute to body dissatisfaction include peer influence, social environment, media, and unrealistic beauty standards.